Beyond the curfew: Diurnal coral reef fish and mesopredator behavioural modifications under artificial light at night in the wild intensifies nocturnal predator-prey interactions - Thibaut Roost; Erin Campbell-Hooper; Frédéric Zuberer; Ricardo Beldade; Therésa M. Jones; Suzanne C. Mills; Stephen E. Swearer (Marine Pollution Bulletin, 2026)

Spatial and temporal variability in δ13C and δ15N signatures of three habitat-forming kelps in the coastal upwelling system of central Chile - Sergio A. Navarrete; Eliseo Fica-Rojas; Fernanda Vargas; Ricardo Beldade; Alejandro Pérez-Matus; Evie A. Wieters (Marine Environmental Research, 2026)

Microbiota of host sea anemones and their associated anemonefish show contrasting responses to a bleaching event - Camille Clerissi; Ricardo Beldade; Anouar Mejait; Anne Haguenauer; Edouard Jobet; Benjamin M. Titus; Suzanne C. Mills (Coral Reefs, 2026)

Fatal Attraction: Light Pollution Creates an Ecological Trap for Wild Fish - Jules Schligler; Tommy Norin; Megan McBride; Fabien Morat; Shaun S. Killen; Stephen E. Swearer; Ricardo Beldade; Suzanne C. Mills (Global Change Biology, 2026)
Ecological traps, poor‐quality habitats that attract animals, significantly threaten ecosystems but have rarely been documented in marine environments. In fish, early life‐history events, such as larval settlement, play a key role in shaping individual survival, population stability, and community interactions. While evidence suggests that late‐stage fish and invertebrate larvae exhibit a phototactic response, the effects of light pollution on larval settlement and survival remain poorly understood. Here, we simulated environmental light pollution on coral reefs using artificial light to examine its impact on fish settlement and post‐settlement consequences. We found that settlement was up to eight times higher onto corals exposed to light pollution compared to those under natural conditions. However, exposure to light pollution reduced recruit survival by half, desynchronized settlement from the full moon and reduced size at settlement. We identified key mechanisms contributing to increased mortality of individuals exposed to artificial light, including disruptions in resting metabolic rhythm and higher predation (due to heightened predator attraction). Additionally, we reveal potential trait compensation in body condition and maximum metabolic rate, traits linked to fitness. However, despite these potential compensatory mechanisms, light pollution functions as a severe ecological trap for fish, attracting individuals into suboptimal environments where they experience higher mortality. This underscores the need to regulate light pollution as a critical environmental stressor.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Environmental change mediates plasticity in offspring traits through maternal effects in a coral reef fish - Daphne Cortese; Clara Diaz; Ricardo Beldade; Shaun S. Killen; Zoe Scholz; Suzanne C. Mills (Science of The Total Environment, 2024)

Artificial Light Increases Nighttime Prevalence of Predatory Fishes, Altering Community Composition on Coral Reefs - Emma Weschke; Jules Schligler; Isla Hely; Thibaut Roost; Jo‐Ann Schies; Ben Williams; Bartosz Dworzanski; Suzanne C. Mills; Ricardo Beldade; Stephen D. Simpson; Andrew N. Radford (Global Change Biology, 2024)
Artificial light at night (ALAN) is an anthropogenic pollutant that is intensifying and expanding in marine environments, but experimental studies of community‐level effects are generally lacking. The inshore, shallow, and clear‐water locations of coral reefs and their diverse photosensitive inhabitants make these ecosystems highly susceptible to biological disturbances; at the same time, their biodiversity and accessibility make them model systems for wider insight. Here, we experimentally manipulated ALAN using underwater LED lights on a Polynesian reef system to investigate the influence on localised nighttime fish communities compared to control sites without ALAN. We collected infrared video censuses of baseline communities prior to manipulation, which we repeated following short‐term (mean of three nights) and prolonged (mean of 25 nights) exposures to ALAN. Short‐term ALAN exposure did not induce any significant alterations to the nighttime fish community, but prolonged ALAN exposure increased nighttime species richness. Species compositions exposed to prolonged ALAN were more dissimilar from their baseline compared to control sites. The difference between community compositions at prolonged ALAN exposure and control sites was not apparent at the family level; instead, it was observed from the composition of trait guilds. Following prolonged ALAN exposure, more diurnal and nocturnal predatory species (piscivores, invertivores, and planktivores)—particularly those that are site‐attached or mobile within reefs—were present in nighttime assemblages. Our experimental findings show that coastal ALAN could cause trophic imbalances and circadian disturbances in localised nighttime reef fish communities. Given that community‐wide consequences were only apparent after prolonged ALAN exposure suggests that management of the duration of artificial lighting could potentially be used to reduce impacts on marine ecosystems.

Variability in oceanographic conditions affecting Mesophotic Ecosystems along the South Eastern Pacific: Latitudinal trends and potential for climate refugia - Lucas de la Maza; Evie A. Wieters; Ricardo Beldade; Mauricio F. Landaeta; Alejandro Perez-Matus; Sergio A. Navarrete (Journal of Marine Systems, 2024)

GABAergic role in the disruption of wild cleaner fish behaviour under high CO2 - José Ricardo Paula; Ligia Cascalheira; Raul Oliveira; Eve Otjacques; Catarina Frazão-Santos; Ricardo Beldade; Suzanne C. Mills; Rui Rosa (Animal Behaviour, 2023)

Aggression of an orange-fin anemonefish to a blacktip reef shark: a potential example of fish mobbing? - Jules Schligler; Agathe Blandin; Ricardo Beldade; Suzanne C. Mills (Marine Biodiversity, 2022)

Deep Heat: A Comparison of Water Temperature, Anemone Bleaching, Anemonefish Density and Reproduction between Shallow and Mesophotic Reefs - Anne Haguenauer; Frédéric Zuberer; Gilles Siu; Daphne Cortese; Ricardo Beldade; Suzanne C. Mills (Fishes, 2021)
French Polynesia is experiencing increasing coral bleaching events in shallow waters triggered by thermal anomalies and marine heatwaves linked to climate change, a trend that is replicated worldwide. As sea surface thermal anomalies are assumed to lessen with depth, mesophotic deep reefs have been hypothesized to act as refuges from anthropogenic and natural disturbances, the ‘deep reef refugia hypothesis’ (DRRH). However, evidence supporting the DRRH is either inconclusive or conflicting. We address this by investigating four assumptions of the DRRH focusing on the symbiotic association between anemones and anemonefish. First, we compare long-term temperature conditions between shallow (8 m) and mesophotic sites (50 m) on the island of Moorea from 2011–2020. Second, we compare the densities of the orange-fin anemonefish, Amphiprion chrysopterus between shallow and mesophotic (down to 60 m) reefs across three archipelagos in French Polynesia. Finally, we compare the percentage of anemone bleaching, as well as anemonefish reproduction, between shallow and mesophotic reefs. We found that the water column was well mixed in the cooler austral winter months with only a 0.19 °C difference in temperature between depths, but in the warmer summer months mixing was reduced resulting in a 0.71–1.03 °C temperature difference. However, during thermal anomalies, despite a time lag in warm surface waters reaching mesophotic reefs, there was ultimately a 1.0 °C increase in water temperature at both 8 and 50 m, pushing temperatures over bleaching thresholds at both depths. As such, anemone bleaching was observed in mesophotic reefs during these thermal anomalies, but was buffered compared to the percentage of bleaching in shallower waters, which was nearly five times greater. Our large-scale sampling across French Polynesia found orange-fin anemonefish, A. chrysopterus, in mesophotic zones in two high islands and one atoll across two archipelagos, extending its bathymetric limit to 60 m; however, orange-fin anemonefish densities were either similar to, or 25–92 times lower than in shallower zones. Three spawning events were observed at 50 m, which occurred at a similar frequency to spawning on shallower reefs at the same date. Our findings of thermal anomalies and bleaching in mesophotic reefs, coupled with mainly lower densities of anemonefish in mesophotic populations, suggest that mesophotic reefs show only a limited ability to provide refugia from anthropogenic and natural disturbances.

Comparative phylogeography of three host sea anemones in the Indo‐Pacific - Madeleine A. Emms; Pablo Saenz‐Agudelo; Emily C. Giles; Remy Gatins; Gerrit B. Nanninga; Anna Scott; Jean‐Paul A. Hobbs; Ashley J. Frisch; Suzanne C. Mills; Ricardo Beldade; Michael L. Berumen (Journal of Biogeography, 2020)
Aim The mutualistic relationship between anemones and anemonefishes is one of the most iconic examples of symbiosis. However, while anemonefishes have been extensively studied in terms of genetic connectivity, such information is lacking entirely for host sea anemones. Here, we provide the first information on the broad‐scale population structure and phylogeographical patterns of three species of host sea anemone, Heteractis magnifica, Stichodactyla mertensii and Entacmaea quadricolor . We evaluate if there is concordance in genetic structure across several distinct biogeographical areas within the Indo‐Pacific region and to what extent the observed patterns may concur with those found for anemonefishes. Location Indo‐Pacific, including the Red Sea. Taxon Heteractis magnifica , S. mertensii and E. quadricolor Methods Microsatellite markers and a combination of statistical methods including Bayesian clustering, isolation by distance (IBD), analysis of molecular variance (AMOVA) and principal components analysis (PCA) were used to determine population structure. The congruence among distance matrices (CADM) method was used to assess similarity in spatial genetic patterns among species. Results Significant population structure was identified in the three host anemone species. Each species is likely composed of at least two genetic clusters corresponding to two biogeographical regions, the Red Sea and the rest of the Indo‐Pacific. Two of the three anemone species seem to be experiencing admixture where the two main clusters overlap (the Maldives). IBD analyses in the Red Sea revealed differences in gene flow among species, suggesting more limited dispersal potential for E. quadricolor than for S. mertensii and H. magnifica . Clonality is documented in S. mertensii for the first time. Main conclusions This research documents the genetic population structure for three ecologically important host sea anemones across the Indo‐Pacific and provides valuable insights regarding their biogeography and evolution. Specifically, we found high levels of genetic divergence between populations across different biogeographical regions, suggesting different evolutionary lineages within species. At the same time, common geographical overlap of population structures suggests similar evolutionary histories among all three species. Interestingly, the observed patterns are congruent to some extent with structure reported for several anemonefish species, reflecting their close ecological association.

Life history, larval dispersal, and connectivity in coral reef fish among the Scattered Islands of the Mozambique Channel - James L. O’Donnell; Ricardo Beldade; Suzanne C. Mills; Hannah E. Williams; Giacomo Bernardi (Coral Reefs, 2017)

Spatial patterns of self‐recruitment of a coral reef fish in relation to island‐scale retention mechanisms - Ricardo Beldade; Sally J. Holbrook; Russell J. Schmitt; Serge Planes; Giacomo Bernardi (Molecular Ecology, 2016)
Oceanographic features influence the transport and delivery of marine larvae, and physical retention mechanisms, such as eddies, can enhance self‐recruitment (i.e. the return of larvae to their natal population). Knowledge of exact locations of hatching (origin) and settlement (arrival) of larvae of reef animals provides a means to compare observed patterns of self‐recruitment ‘connectivity’ with those expected from water circulation patterns. Using parentage inference based on multiple sampling years in Moorea, French Polynesia, we describe spatial and temporal variation in self‐recruitment of the anemonefish Amphiprion chrysopterus , evaluate the consistency of net dispersal distances of self‐recruits against the null expectation of passive particle dispersal and test the hypothesis that larvae originating in certain reef habitats (lagoons and passes) would be retained and thus more likely to self‐recruit than those originating on the outer (fore) reef. Estimates of known self‐recruitment were consistent across the sampling years (~25–27% of sampled recruits). For most (88%) of these self‐recruits, the net distance between hatching and settlement locations was within the maximum dispersal distance expected for a neutrally buoyant passive particle based on the longest duration of the larval dispersive phase and the average direction and speed of current flow around Moorea. Furthermore, a parent of a given body size on the outer (fore) reef of Moorea was less likely to produce self‐recruits than those in passes. Our findings show that even a simple dispersal model based on net average flow and direction of alongshore currents can provide insight into landscape‐scale retention patterns of reef fishes.

Incorporating historical and ecological genetic data for leopard grouper (Mycteroperca rosacea) into marine reserve design in the Gulf of California - Alexis M. Jackson; Adrian Munguía-Vega; Ricardo Beldade; Brad E. Erisman; Giacomo Bernardi (Conservation Genetics, 2015)

Isolation and characterization of 8 novel microsatellites for the black abalone, Haliotis cracherodii, a marine gastropod decimated by the withering disease - Ricardo Beldade; Christy A. Bell; Peter T. Raimondi; Maya K. George; C. Melissa Miner; Giacomo Bernardi (Conservation Genetics Resources, 2012)

Isolation and characterization of eight polymorphic microsatellite markers from the orange-fin anemonefish, Amphiprion chrysopterus - Ricardo Beldade; Sally J. Holbrook; Russell J. Schmitt; Serge Planes; Giacomo Bernardi (Conservation Genetics Resources, 2009)

Multiple paternity and competition in sympatric congeneric reef fishes, Embiotoca jacksoni and E. lateralis - CÉLINE M. O. REISSER; RICARDO BELDADE; GIACOMO BERNARDI (Molecular Ecology, 2009)
The black surfperch Embiotoca jacksoni and the striped surfperch E. lateralis (Embiotocidae, Perciformes) are livebearing temperate reef fishes that live sympatrically over a large portion of their distribution range, where they exhibit strong ecological competition. In order to assess whether mating strategies reflect competition, we investigated multiple paternity in these two species in an area of sympatry. We sampled 24 pregnant females (12 for each species) in Monterey Bay, California, used microsatellite analysis and assessed paternity with the COLONY software. While broods are relatively small (12 to 36 offspring), they were always sired by multiple fathers (2 to 9), with no correlation between the size of a brood and the number of fathers. The number of sires for each brood was not significantly different between the two species (approximately 3.5 sires per brood). We tested the deviation from stochasticity of fathered offspring for each father in one brood. Results showed a significant deviation for both E. jacksoni and E. lateralis . However, this deviation was not found to be significant between species. The striking similarity in the dynamics of multiple paternity in these species, when sampled in sympatry, may result from several alternative scenarios, including phylogenetic inertia, reproductive behaviour, and ecological competition.

Historical biogeography and speciation in the Creole wrasses (Labridae, Clepticus) - Ricardo Beldade; J. B. Heiser; D. R. Robertson; J. L. Gasparini; S. R. Floeter; G. Bernardi (Marine Biology, 2009)

Vertical structure of very nearshore larval fish assemblages in a temperate rocky coast - Rita Borges; Ricardo Beldade; Emanuel J. Gonçalves (Marine Biology, 2007)